The collected letters of William Morris : Volume II: 1885-1888 - Morris, William (Princeton Legacy Library, 1987)
""Cover ""; ""Contents ""; ""The Letters 1885-1888 ""; ""Appendix A. The Manifesto of the Socialist League ""; ""Appendix B. An Essay on Printing by Emery Walker ""; ""Index of Correspondents ""; ""Subject Index